A two‐stage adaptive clinical trial design with data‐driven subgroup identification at interim analysis. (24th March 2022) - Johnston, Sarah E.; Lipkovich, Ilya; Dmitrienko, Alex; Zhao, Yan Daniel
Abstract: In this paper, we consider randomized controlled clinical trials comparing two treatments in efficacy assessment using a time to event outcome. We assume a relatively small number of candidate biomarkers available in the beginning of the trial, which may help define an efficacy subgroup which shows differential treatment effect. The efficacy subgroup is to be defined by one or two biomarkers and cut‐offs that are unknown to the investigator and must be learned from the data. We propose a two‐stage adaptive design with a pre‐planned interim analysis and a final analysis. At the interim, several subgroup‐finding algorithms are evaluated to search for a subgroup with enhanced survival for treated versus placebo. Conditional powers computed based on the subgroup and the overall population are used to make decision at the interim to terminate the study for futility, continue the study as planned, or conduct sample size recalculation for the subgroup or the overall population. At the final analysis, combination tests together with closed testing procedures are used to determine efficacy in the subgroup or the overall population. We conducted simulation studies to compare our proposed procedures with several subgroup‐identification methods in terms of a novel utility function and several other measures. This research demonstrated the benefit of incorporating data‐driven subgroup selection into adaptive clinical trial designs.